A systematic review of the effects of acupuncture on xerostomia and hyposalivation - Zainab Assy; Henk S. Brand (BMC, 2018)
Abstract Background Saliva is fundamental to our oral health and our well-being. Many factors can impair saliva secretion, such as adverse effects of prescribed medication, auto-immune diseases (for example Sjögren's syndrome) and radiotherapy for head and neck cancers. Several studies have suggested a positive effect of acupuncture on oral dryness. Methods Pubmed and Web of Science were electronically searched. Reference lists of the included studies and relevant reviews were manually searched. Studies that met the inclusion criteria were systematically evaluated. Two reviewers assessed each of the included studies to confirm eligibility and assessing the risk of bias. Results Ten randomized controlled trials investigating the effect of acupuncture were included. Five trials compared acupuncture to sham/placebo acupuncture. Four trials compared acupuncture to oral hygiene/usual care. Only one clinical trial used oral care sessions as control group. For all the included studies, the quality for all the main outcomes has been assessed as low. Although some publications suggest a positive effect of acupuncture on either salivary flow rate or subjective dry mouth feeling, the studies are inconclusive about the potential effects of acupuncture. Conclusions Insufficient evidence is available to conclude whether acupuncture is an evidence-based treatment option for xerostomia/hyposalivation. Further well-designed, larger, double blinded trials are required to determine the potential benefit of acupuncture. Sample size calculations should be performed before before initiating these studies.